Synthesis and characterization of novel ZrO2-SiO2 mixed oxides - Milena Araújo Ferreira e Santos; Ivon Pinheiro Lôbo; Rosenira Serpa da Cruz (Materials Research, 2014)
In this study the mixed oxides ZrO2-SiO2, were synthesized by the sol-gel method with a molar ratio of 95:5 (Si/metal) and characterized by X-ray diffraction, absorption-desorption of N2, Fourier transform infrared spectroscopy, thermal gravimetric analysis, temperature-programmed desorption of ammonia, and acidity test by titration. The synthesized materials, which are amorphous to X-rays, are composed of a mixture of micro- and mesopores. They show a higher acid strength than the separate oxides, indicating that the ZrO2 is highly dispersed in the silica matrix.